CAUSES OF RECRUITMENT OF CHILD SOLDIERS IN NEPAL: AN ANALYSIS FROM CHILD RIGHTS NGO PERSPECTIVES - Sanjaya Aryal (Fakultas Hukum Universitas Trisakti, 2008)
More than a decade long armed conflict in Nepal put a greater impact on Nepalese children. Hundreds of children lost their lives, thousands injured, lost their parents and displaced, and devoid of basic services such as education and health care. One of the worst forms of impact of the armed conflict in Nepalese children is their recruitment and use as child soldiers in armed forces and armed groups. Both the parties to the conflict, i.e. state actor (Nepalese government security forces) and non-state entity (rebel group-Communist Party of Nepal (Maoist)) recruited and used the child soldier in many ways and forms. From the study it is found that, though the nature and causes of armed conflict, intensity of use of child soldiers in heinous atrocities, and intensity of recruitment and abduction of children in Nepal is different and less than any of the African conflicts, but the causes of recruitment are found similar, i.e. multidimensional. NGOs have come together and formed a working group to bring synergy in their individual efforts in reintegration of the former child soldiers. However, even after around two years of initiation of peace process in the country, formal release and reintegration of those victimized children has not started yet and the children are either still in the cantonment sites waiting for their release or they have informally released and associated with semipolitical or paramilitary wings of Maoist. Hence, the human rights violations of these child soldiers are still continued.